The role of tahfidz teacher in improving al-qur'an memorization at Riyadh El-Jannah Islamic School Bekasi - Rahmat, Muhammad Nur; Suharsiwi, Suharsiwi; Susilahati, Susilahati (Kepompong Children Centre Journal, 2024)
This article aims to find out the Obstacles teachers feel in guiding students to memorize the Al-Qur'an and what strategies teachers use to help their students memorize the Al-Qur'an. The research used is qualitative with a descriptive analysis approach. The research results show that Tahfiz Riyadh El-Jannah teachers face various obstacles, such as students who are not yet fluent in reading the Koran, lack of student motivation, and differences in student intelligence. However, in dealing with these obstacles, teachers use strategies that are used by Tahfiz teachers, including time management, choosing a good place and environment, and determining the material to be memorized regularly. In educating students to memorize the Al-Qur'an consistently, it is essential to first develop a love for the Al-Qur'an through example or modern education to support memorizing the Al-Qur'an.